The Reality of Using the Blended Learning Strategy in Teaching Chemistry for Secondary School Students from the point of View of Teachers and Educational Supervisors in The Kingdom of Saudi Arabia - Alamri, Wardah Gharman; Felemban, Ghadir Zinedine; Felemban, Fadwa (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to reveal the reality of using the blended learning strategy in teaching chemistry at the secondary level from the point of view of female teachers and educational supervisors. The study relied on the analytical descriptive approach to achieve its objectives, as a questionnaire was prepared for this purpose, consisting of 39 paragraphs distributed on three main axes as follows: The first axis is the degree of applying the blended learning strategy, and it consists of (11) phrases, and the second axis is the degree of importance of the requirements for applying the strategy Blended learning, consisting of (10) phrases, and the third axis is the degree of obstacles to applying the blended learning strategy, and it consists of (18) phrases, while it was distributed to a sample of 96 participants (teacher, educational supervisor), and the results of data analysis revealed a high degree in The general average of applying the blended learning strategy from the point of view of teachers and educational supervisors, and a medium degree in the importance of the requirements of applying the blended learning strategy, while the obstacles to applying the blended learning strategy from the point of view of teachers and educational supervisors came to a large extent. The results also showed that there was no effect for the variables (job title, qualification, years of experience), and for the bilateral and tripartite interaction between them on the degree of applying the blended learning strategy, and on the degree of obstacles to applying the blended learning strategy, while a statistically significant difference was found between the average responses of the sample members on the degree of importance of the requirements The application of the blended learning strategy according to the educational qualification variable, and there was no effect for the variables of job and years of experience and for the bilateral and tripartite interaction between all variables in the degree of importance of the requirements of applying the blended learning strategy.
Keywords: Reality; The blended learning Strategy; Teaching Chemistry; Secondary School; Teachers and Educational Supervisors